Interdependent self‐construal moderates the relationship between pro‐generation investment and future orientation: A cross‐cultural comparison. Issue 7 (28th July 2022) - Chen, Yidi; Gao, Lingling; Sheng, Zhengyu; Ma, Jinjin; Guo, Xiaohan (Hannah); Lippke, Sonia; Gan, Yiqun
Abstract: Introduction: Cultural orientation and interdependent self‐construal can moderate the relationship between perceived pro‐generation investment and future orientation of young adults. To test how interdependent self‐construal moderate the relationship between pro‐generation investment and future orientation of young adults from two different cultural ecologies was the aim of the current study. Methods: A cross‐cultural comparison was conducted among study participants from China, Germany, and the United States. Interdependent self‐construal, perceived pro‐generation investment by parents (parental investment), and future orientation were measured. Cross‐cultural data were collected from 205 college students in China, a collectivist culture, and 169 college students in Germany ( n = 50) and the United States ( n = 119), which are individualist cultures. We examined a three‐way interaction with cultural orientation and interdependent self‐construal as moderators in the relationship between perceived parental investment and future orientation. Results: In the collectivist cultural context, there appeared no moderating effect of interdependent self‐construal on the relationship between perceived parental investment and future orientation, although interdependent self‐construal and perceived parental investment predicted future orientation. In the individualistic cultural context, there was a moderating effect. For individuals high in interdependent self‐construal, future orientation remained stable as perceived parental investment increased. For individuals low in interdependent self‐construal, future orientation decreased as perceived parental investment increased. Conclusions: The findings have practical implications in that parents should follow the cultural orientation of their background and provide their children with individualized investment and education to shape the future orientation of their offspring.